2006
DOI: 10.3173/air.15.331
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Fuzzy Approaches for Modeling the Wet Season Tropical Rainfall

Abstract: Information on rainfall variations is a matter of great importance in agricultural countries. Climate and rainfall are non-linear natural phenomena whose measurement leads to complex data, primarily due to noise patterns and distribution heterogeneity. Therefore, it is difficult to develop an appropriate model in practice by using conventional modeling techniques. This study presents the use of a neuro-fuzzy system for modeling wet season tropical rainfall. The advantage of this technique was the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They showed that the same error occurred in both models. The neurofuzzy system was employed by Annas et al (2006) [12] to model tropical rainfall in the wet season. The low root mean squared error values of the models showed that the model forecasts are reliable.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the same error occurred in both models. The neurofuzzy system was employed by Annas et al (2006) [12] to model tropical rainfall in the wet season. The low root mean squared error values of the models showed that the model forecasts are reliable.…”
Section: Introductionmentioning
confidence: 99%
“…A neural-fuzzy system for modeling wet season tropical rainfall has been used [23]. Fallah-Ghalhary et al has used fuzzy inference system in the northeast of Iran for forecasting rainfall time series based on the rainfall data [24].…”
Section: Introductionmentioning
confidence: 99%